Efficacy and mechanism of Baicao Fuyanqing suppository on mixed vaginitis based on 16S rRNA and metabolomics - Wang, Qi; Wang, Pengjiao; Yuan, Minyan; Zhang, Min; Zhang, Shuo; Sun, Xiaodong; Shang, Leyuan; Liu, Yujie; Zhao, Yanni; Jiang, Nan; Gao, Xiuli (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Mixed vaginitis is the infection of the vagina by at least two different pathogens at the same time, both of which contribute to an abnormal vaginal environment leading to signs and symptoms. Baicao Fuyanqing suppository (BCFYQ) is a Miao ethnomedicine, used to treat various vaginitis. The aim of this study was to investigate the efficacy and possible mechanism of BCFYQ in the treatment of mixed vaginitis based on 16S rRNA high-throughput sequencing and metabonomics.Methods: Escherichia coli and Candida albicans were used to establish mixed vaginitis model in SD rats. Three groups of low, medium and high doses (0.18/0.36/0.64 g.kg -1 ) were established, and administered vaginally once a day for 6 consecutive days. After the last administration, vaginal pH and IL-1β, IL-2, IL-13 and IgA levels were measured, and the vaginal tissue was examined pathologically. In addition, the vaginal flora was characterised by 16S rRNA, and endogenous metabolites in the vaginal tissue were detected by UHPLC-Q-Exactive MS.Results: Compared with the model group, BCFYQ can reduce the vaginal pH of rats, make it close to the normal group and improve the damaged vaginal epithelial tissue. The results of ELISA showed that BCFYQ decreased the levels of IL-1 β and IL-2 and increased the levels of IL-13 and IgA (P<0.05). In addition, BCFYQ may increase the abundance of vaginal flora, especially Lactobacillus.The differential metabolite enrichment pathway suggests that the therapeutic mechanism of BCFYQ is mainly related to lipid metabolism and amino acid metabolism.Our research shows that BCFYQ has a good therapeutic effect on mixed vaginitis. It repairs the damaged vaginal mucosa by regulating the vaginal flora and lipid metabolism disorders to improve the local immune function of the vagina and inhibit the growth and reproduction of pathogens.